2018
DOI: 10.1002/jcp.27828
|View full text |Cite
|
Sign up to set email alerts
|

The possible role of bacteria, viruses, and parasites in initiation and exacerbation of irritable bowel syndrome

Abstract: Irritable bowel syndrome (IBS) is a prolonged and disabling functional gastrointestinal disorder with the incidence rate of 18% in the world. IBS could seriously affect lifetime of patients and cause high economic burden on the community. The pathophysiology of the IBS is hardly understood, whereas several possible mechanisms, such as visceral hypersensitivity, irregular gut motility, abnormal brain–gut relations, and the role of infectious agents, are implicated in initiation and development of this syndrome.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0
5

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(33 citation statements)
references
References 172 publications
(329 reference statements)
1
24
0
5
Order By: Relevance
“…E. coli and S. aureus bacteria, gramnegative and gram-positive bacteria, respectively, were selected for this study. These two bacteria can be found in abundance in nature; in addition, they cause various infections including diarrhea, wound infection and septicemia in humans (13,14). After placing E. coli in an electromagnetic field of 1mT, the number of colonies was increased in comparison to the control group that had not been The results obtained in the present study are in line with the results obtained by Nawrotek and his colleagues.…”
Section: Discussionsupporting
confidence: 91%
“…E. coli and S. aureus bacteria, gramnegative and gram-positive bacteria, respectively, were selected for this study. These two bacteria can be found in abundance in nature; in addition, they cause various infections including diarrhea, wound infection and septicemia in humans (13,14). After placing E. coli in an electromagnetic field of 1mT, the number of colonies was increased in comparison to the control group that had not been The results obtained in the present study are in line with the results obtained by Nawrotek and his colleagues.…”
Section: Discussionsupporting
confidence: 91%
“…Studies suggested that the organism's role in nonspecific gastrointestinal symptoms such as diarrhea, constipation, abdominal pain, nausea, and vomiting together with extra‐intestinal manifestations, particularly urticaria . The role of Blastocystis in the development of inflammatory bowel disease (IBD) and irritable bowel syndrome (IBS) was also reported recently, but there was not good evidence supporting the association of Blastocystis with gastrointestinal disorders. Thus Blastocystis is still considered as a nonpathogenic parasite .…”
Section: Discussionmentioning
confidence: 99%
“…Unter physiologischen Bedingungen stellen Tight Junctions im Darm die entscheidende Determinante der mukosalen Barrierefunktion dar. Durch Infektion [20] [21], genetische Prädisposition [22][23] [24], zentralnervöse Veränderungen wie eine erhöhte Stressachsenaktivierung [25], Angsterkrankungen oder Depression [26] kann es zu Veränderungen im Darmepithel kommen, was wiederum eine erhöhte Gefahr für intestinale Infektionen mit sich bringt. Eine erhöhte Permeabilität der Tight Junctions, welche bei RDS u. a. auf Veränderungen der Claudin-und Occludin-Expression zurückzuführen ist [27], führt zur Rekrutierung von Immunzellen wie dendritischen Zellen oder Mastzellen, die durch die Ausschüttung proinflammatorischer Zytokine wie Interleukine, Histamin oder Serotonin eine lokale Inflammation hervorrufen können [28].…”
Section: Permeabilitätunclassified